Use of a Heparin Nomogram for Treatment of Patients with Venous Thromboembolism in a Community Hospital - de Groot, Marco R.; Büller, Harry R.; ten Cate, Jan W.; Kooy, Marinus van Marwijk (Thrombosis and Haemostasis, 1998)
Background: The application of a heparin dosing nomogram in the treatment of patients with venous thromboembolism resulted in improvement of heparin therapy in clinical research settings. In 1992 a heparin nomogram was introduced in our hospital, which is a community hospital where anticoagulant therapy is supervised by the attending physicians. We studied whether comparable improvements were achieved in such a non-surveyed clinical setting. Methods: Patients were identified from computerized discharge records, and classified into a pre-nomogram (discharged in 1990 or 1991) and a nomogram patient group (discharged in 1993 or 1994). The use of the nomogram was encouraged but the application remained on a voluntary basis. Since the definition of the target APTT range was different in the pre-nomogram period as compared to the nomogram period, a formal analysis of pre- and post-nomogram results was not considered justified. Results: The APTT ratio, six hours after the start of heparin treatment, was below the predefined lower limit in 72% of 127 patients in the pre-nomogram group and in 13% of 127 patients in the nomogram group. During 1043 days heparin therapy in the nomogram group the morning APTT ratio was subtherapeutic in 8%. In 58% of all APTT results the physician responded according to the nomogram. The subsequent APTT was in the target range in 64% of the cases compared to 31% if the adjustement was not performed according to the nomogram (P<.0001). Major bleeding episodes occurred in 3.1% in the pre-nomo-gram period and in 0.7% in the nomogram period.Conclusion: The present study shows that the introduction of a heparin dosing nomogram in a non-research clinical setting results in more adequate heparin anticoagulation with low risks of bleeding.